2018
DOI: 10.1108/dta-03-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

The subjective side of DiDIY: the profile of makers in network marketers communities

Abstract: Purpose The purpose of this paper is to focus on the profile of DiDIYers and the antecedents of digital do it yourself (DiDIY) in Network Marketing Direct Selling Organizations (NMDSO). Design/methodology/approach A two-step research design allowed the detection of DiDIYers strictu sensu (i.e. digital makers). After collecting data about the attitudes and the actual use of digital technology (DT) by network marketers through an online survey, an open-ended interview technique made it possible to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Secondly, the analysis and rise of e-commerce business conditions, from the domestic factors more research, from the system policy to the enterprise's own innovation and reform ability comprehensive research, and the rise of e-commerce enterprises, not only need our own efforts, but also should have mutual exchanges and mutual promotion process. Foreign scholars should strengthen the study of business enterprises, analyze the problems, put forward feasible strategies, and explore a new path for the healthy rise of e-commerce mode in the light of the current economic situation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the analysis and rise of e-commerce business conditions, from the domestic factors more research, from the system policy to the enterprise's own innovation and reform ability comprehensive research, and the rise of e-commerce enterprises, not only need our own efforts, but also should have mutual exchanges and mutual promotion process. Foreign scholars should strengthen the study of business enterprises, analyze the problems, put forward feasible strategies, and explore a new path for the healthy rise of e-commerce mode in the light of the current economic situation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The results found that gender has no impact on the similarity of social networking sites. Guerini and Minelli [5] examined the subjective side of DiDIY (Digital Do It Yourseft): the profile of creators in the network marketer community, a study on digital marketers. The study found that DiDIYer's initial profile in the network marketing community was suitable for further comparative study.…”
Section: Introductionmentioning
confidence: 99%